Detection of cassava brown streak ipomoviruses in aphids collected from cassava plants - Nanyiti, Sarah; Kabaalu, Richard; Alicai, Titus; Abidrabo, Phillip; Seal, Susan E.; Bouvaine, Sophie; Bailey, Andy M.; Foster, Gary D. (Frontiers in Sustainable Food Systems, 2023)
1 Abstract Cassava is an important staple food in Africa and 800 million people depend on the crop as a source of carbohydrates. However, cassava suffers low average yields, caused by a number of factors including susceptibility to pests and diseases. Among the viral diseases are cassava brown streak disease (CBSD) caused by ipomoviruses (family Potyviridae) Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV), collectively known as Cassava brown streak ipomoviruses (CBSI’s). Spread of CBSD is mainly through planting infected materials in addition, vector transmission of the CBSI’s by the whitefly insect vector Bemisia tabaci has been reported. However, experimental transmission efficiencies with the whitefly vector are usually low at about 22%. Recent research has shown occurrence of a DAG motif associated with aphid transmission in other potyviruses, within the coat protein gene of CBSV. Arising from these previous findings, this study aimed to explore the possibility that CBSI’s may be transmitted by aphids in addition to whiteflies. Cassava plants were assessed for occurrence of CBSD and aphids as potential alternative vectors for CBSI’s. Aphids were collected from CBSD-symptomatic and non-symptomatic cassava plants within farmers’ fields in Uganda during the months of April-July 2020. The aphids were analyzed for the presence of CBSI’s by reverse transcriptase-polymerase chain reaction (RT-PCR) and to determine aphid species using MtCOI barcoding. Aphids were found in cassava plant fields at 35 locations in nine districts in Uganda and on 11 other plant species within or adjacent to cassava fields. Molecular characterization of the aphid species confirmed the presence of three different aphid species found in different fields in Uganda including Aphis solanella, Aphis fabae mordvilkoi and Rhopalosiphum aphid. The sequences for the aphids MtCOI in which CBSI’s were detected were submitted to Genbank under accession numbers OP223337-40. Both UCBSV and CBSV were detected by RT-PCR in aphids collected from cassava fields with CBSD-affected plants. The CBSI’s were detected in a total of 14 aphid samples collected from 19 CBSD symptomatic plants. Results suggest ability of aphids to acquire CBSI’s, but transmission experiments are required to further investigate their vector potential.